Implementation of Learning Model Cooperative Learning Teams Games Tournament Collaborates With Lottery Card - Lestari, Oktaviary Wahyu; Yunikawati, Nur Anita (Classroom Action Research Journal (CARJO), 2017)
Economic studies in class XI IPS 1 on MAN 3 Malang apply conventional learning methods and discussion groups. These methods are already focused on student learning activities, but only a few students are able to demonstrate their academic ability. The existence of these problems resulted in students who are still unable to achieve minimal competence. Therefore, needed learning models that can improve student learning outcomes. The purpose of this research was conducted to describe the learning results of students of Class XI IPS 1 MAN 3 Malang cognitive domain in economic subjects with applied learning model Cooperative Learning Teams Games Tournament collaborated with Lottery Card. The results is: 1) On cycle 1 an increase in percentage of completed learning 3.85% when pretest become 76% when the post-test; 2) At cycle 2 an increase in percentage of completed learning 7.69% when pretest be 100% on the post-test. The first conclusion of this research is that the application of the Cooperative learning model of the Learning Teams Games Tournament collaborated with Lottery Card on economic subjects can be applied well in class XI IPS 1 MAN 3 Malang, both the application of Cooperative learning model of the Learning Teams Games Tournament collaborated with Lottery Card can improve the students learning outcomes on economic subjects of Class XI IPS 1 MAN 3 Malang.Keyword: Cooperative Learning, Teams Games Tournament, Lottery Card, The Result of the Study.DOI:Â 10.17977/um013v1i22017p099